Loss, Damage and Responsibility after COP21: All Options Open for the Paris Agreement. Issue 2 (July 2016) - Mace, M.J.; Verheyen, Roda
Abstract : The issue of 'loss and damage' has proven to be a legally and politically challenging one within the international climate change regime. This article presents a brief history of the issue, and reviews related Paris outcomes, focusing on the issues of compensation and liability, governance, financial support, insurance and displacement. It concludes that despite paragraph 51 of Decision 1/CP.21 adopting the Paris Agreement, all options remain open for the development of a system under the climate regime that can address the underlying concerns raised by small island developing States and others in calling for a system of compensation and liability. In the context of the 1.5 °C temperature limit and increasing climate impacts, this article also highlights the need for the Warsaw International Mechanism to play an active role in quantifying the scale of loss and damage that is projected from human‐induced climate change in different regions and in different national contexts, over different time frames and at different emission pathways, and in sharing developments in attribution science, to help in the design of approaches to address loss and damage that are suited to assisting the most vulnerable developing country parties and to underscore the need for urgent emission reductions.